Perspective for a New Bioinspired Permanent Adhesive for dry Conditions - Insights in the Glue Producing Japanese art of Defence System of the Oita Salamander Hynobius dunni - von Byern, Janek; Farkaš, Robert; Steinort, Daniel; Greistorfer, Sophie; Eckhard, Margret; Cyran, Norbert (Frontiers in Mechanical Engineering, 2021)
Novel medical bioadhesives are proposed to fulfil numerous ideals as being biocompatible, non-toxic, include tissue healing and regeneration characteristics, have high mechanical properties onto different surfaces and other important key features. Mussel-inspired adhesives have provided the basis for many new applications under wet conditions. In contrast, the defence secretion system in amphibians may provide potential for novel fast-curing secretion able to adhere to surfaces under dry conditions. With the microanatomical and histochemical characterization of the endemic Japanese Oita salamander Hynobius dunni details on its anatomical organization, the nature of the chemical composition of both glue-producing glands and its divergence to the other well-characterized species Plethodon shermani are discussed. The study shows that the cutaneous glands of both glue-producing salamanders (H. dunni and P. shermani) exhibit certain morphological and histochemical similarities. Nevertheless, clear differences exist between the two species, especially with regard to the sugar composition of the mucous glands and the pH level of the granular glands. Moreover, the adhesive secretions of H. dunni show a clear reactivity to Arnow staining (indicating the presence of L-DOPA), which is lacking in P. shermani. This is the first indication of the presence of L-DOPA in the adhesive secretions of a terrestrial vertebrate, which has thus far only been found for marine invertebrates, such as mussels and polychaetes.